STANDAR AKUNTANSI INTERNASIONAL: HARMONISASI VERSUS KONVERGENSI - Kurniawati, Novi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
Globalization brings changes to the capital markets and business operations across borders. State sector in a multinational company is required to make financial reports that can be received throughout the world, but in every country have their own accounting standards are of course different between a country's accounting standards with other countries. For it requires the international accounting standards, so that financial disclosures made by a company in a country multinational globally acceptable. Application of international accounting standards is very difficult because of differences in both legal, environmental, social and economic conditions between one country to another and to bridge it then requires the process of harmonization and convergence. There is a difference between the process of harmonization and convergence of international accounting standards. Only at the stage of harmonization, alignment of accounting standards issued by standard-setting bodies in each country with International Accounting Standard (IAS), while convergence is the next stage of the harmonization of accounting standards which are expected in the context of international standards aimed at eventually there would be only one standard. The process of harmonization and convergence of international accounting standards is not easy to just run, many obstacles and criticisms of the process of harmonization and convergence in which the harmonization and convergence is only suitable for large companies are multinational companies rather than small and medium enterprises, although there are also advantages that can be obtained from the harmonization and convergence of international accounting standards, among others comparable financial reporting, increase transparency, reduce costs and increase global investment capital.